The Role of Non-animal Origin Feed Ingredients in Transmission of Viral Pathogens of Swine: A Review of Scientific Literature - Gordon, Rebecca K.; Kotowski, Ingrid K.; Coulson, Kari F.; Link, Donald; MacKenzie, Alexandra; Bowling-Heyward, Joyce (Frontiers in Veterinary Science, 2019)
The emergence of porcine epidemic diarrhea in commercial swine in North America and growing concerns about the potential for the introduction of African swine fever from China, the European Union, or other affected regions has put a spotlight on the possible role of contaminated feed and feed ingredients in the introduction and transmission of viral swine pathogens. This paper systematically reviews the scientific literature regarding whether non-animal origin ingredients of commercial swine feed could introduce or transmit viral pathogens of swine into or within the United States. The purpose of this review is to identify, evaluate, and summarize the relevant scientific knowledge, published through March 2018, and to identify information gaps and research needs, thereby making the available evidence more accessible to policy makers, the swine industry, and the scientific community. A total of 26 documents were selected for the final review process, which included experimental studies, case reports, epidemiological investigations, and scientific opinion, among others. The review found that the scientific literature has addressed some critical experimental questions pertaining to transmission of swine viruses via feed and feed ingredients, but the current body of scientific knowledge lacks conclusive evidence of virus contamination of non-animal origin feed ingredients of commercial swine feed, particularly for imported commodities, and further investigation into the epidemiology of virus transmission via feed to swine under field conditions through natural feeding behavior is warranted. Additional studies of how imported ingredients of commercial swine feed are sourced, processed, transported and, thus, contaminated prior to importation into the United States are needed. Moving forward, studies designed to examine the likely source(s) of contamination and subsequent virus mitigation steps in processing and post-processing may be the most fruitful focus of research.